(untitled) (Palestine Issues on Indonesian Society, 2025)
This paper explores the instrumentalization of the Palestinian cause in Indonesian political discourse, analyzing how politicians use the conflict to rally domestic support and position themselves on the international stage. By examining speeches, campaigns, and legislative actions, this study identifies the ways in which Palestinian solidarity is framed within national politics, particularly in relation to Indonesia’s Muslim identity and its role in global geopolitics. The paper analyzes how political parties, especially Islamic-oriented parties, incorporate the Palestinian issue into their rhetoric, linking it to nationalistic themes such as anti-imperialism, justice, and solidarity with oppressed peoples. It also examines how the Palestinian cause is used to criticize domestic political rivals, both in the context of foreign policy and social justice. Additionally, the paper assesses the implications of this rhetoric on Indonesia’s relationship with international powers, particularly in relation to its standing in the Muslim world and its diplomatic ties with Israel and the United States. The study reveals how the Palestinian issue is utilized as a political tool within domestic Indonesian political strategies, reflecting broader trends in the use of foreign policy for domestic political gain.